2017
DOI: 10.1111/ijpo.12231
|View full text |Cite
|
Sign up to set email alerts
|

Foetal fractional thigh volume: an early 3D ultrasound marker of neonatal adiposity

Abstract: SummaryBackground: The predisposition for obesity is suggested to originate in the prenatal period. Prenatal markers are needed to identify foetuses at risk for neonatal adiposity, as early marker of childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, no automatic or semi-automatic methods for fetal fat quantification in US or MRI have been developed. Roelants et al [24] described automated methods for US limb soft-tissue quantification, a surrogate for subcutaneous AT lipid deposition. Mack et al [22] presented a semi-automatic method for fractional limb volume assessment and showed that it reduces observer variability and annotation time.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no automatic or semi-automatic methods for fetal fat quantification in US or MRI have been developed. Roelants et al [24] described automated methods for US limb soft-tissue quantification, a surrogate for subcutaneous AT lipid deposition. Mack et al [22] presented a semi-automatic method for fractional limb volume assessment and showed that it reduces observer variability and annotation time.…”
Section: Introductionmentioning
confidence: 99%